Durability of a low shrinkage TEGDMA/HEMA-free resin composite system in Class II restorations. A 6-year follow up. Issue 8 (August 2017) - van Dijken, Jan W.V.; Pallesen, Ulla
Abstract: Objective: The objective of this randomized controlled prospective trial was to evaluate the durability of a low shrinkage and TEGDMA/HEMA-free resin composite system in posterior restorations in a 6-year follow up. Methods: 139 Class II restorations were placed in 67 patients with a mean age of 53 years (range 29–82). Each participant received at random two, as similar as possible, Class II restorations. In the first cavity of each pair the TEGDMA/HEMA-free resin composite system was placed with its 3-step etch-and-rinse adhesive (cmf-els). In the second cavity a 1-step HEMA-free self-etch adhesive was used (AdheSe One F). The restorations were evaluated using slightly modified USPHS criteria at baseline and then yearly during 6 years. Caries risk and parafunctional habits of the participants were estimated. Results: Three molar teeth showed mild post-operative sensitivity during 3 weeks for temperature changes and occlusal forces. After 6 years, 134 Class II restorations were evaluated. Twenty-one restorations, 8 cmf-els (11.4%) and 13 ASE-els (20%) failed during the 6 years (p < 0.0001). The annual failure rates were 1.9% and 3.3%, respectively. The main reasons for failure were fracture followed by recurrent caries. Most fractures and all caries lesions were found in high risk participants. Significance: The Class II resin composite restorations performed with the new TEGDMA/HEMA-free low shrinkage resin composite system showed good durability over six years.